The APOE isoforms differentially shape the transcriptomic and epigenomic landscapes of human microglia xenografted into a mouse model of Alzheimer’s disease - Kitty B. Murphy; Di Hu; Leen Wolfs; Susan K. Rohde; Gonzalo Leguía Fauró; Ivana Geric; Renzo Mancuso; Bart De Strooper; Sarah J. Marzi (Nature Communications)
Abstract Microglia play a key role in the response to amyloid beta in Alzheimer’s disease (AD). In this context, the major transcriptional response of microglia is the upregulation of APOE, the strongest late-onset AD risk gene. Of its three isoforms, APOE2 is thought to be protective, while APOE4 increases AD risk. We hypothesised that the isoforms change gene regulatory patterns that link back to biological function by shaping microglial transcriptomic and chromatin landscapes. We use RNA- and ATAC-sequencing to profile gene expression and chromatin accessibility of human microglia xenotransplantated into the brains of male APP NL-G-F mice. We identify widespread transcriptomic and epigenomic differences which are dependent on APOE genotype and are corroborated across the profiling assays. Our results indicate that impaired microglial proliferation, migration and immune responses may contribute to the increased risk for late-onset AD in APOE4 carriers, while increased phagocytic capabilities and DNA-binding of the vitamin D receptor in APOE2 microglia may contribute to the isoform’s protective role.